The influence of preliminary heat treatment on morphology of carbon layer formed on surface of chlorinated polyvinyl chloride under the impact of a high-power ion beam - V. S. Kovivchak; A. A. Parygin (Омский научный вестник)
The effect of preliminary heat treatment on the morphology of carbon layer formed on the surface of chlorinated polyvinyl chloride with the addition of ferrocene (10 % of polymer weight) under the impact of a high-power nanosecond-durable ion beam has been studied. Preliminary exposure of samples in an oven at different temperatures for 1 hour leads to partial dehydrochlorination of the surface layer of the polymer film and interchain crosslinking, creating centers for the start of the carbonization reaction, and thus affects the formation of carbon nanostructures during subsequent irradiation with a high-power ion beam. The possible mechanism of carbon nanostructures formation from chlorinated polyvinyl chloride under the impact of a high-power ion beam and the mechanism of the influence of preliminary heat treatment on it are considered. It has been established that different heat treatment temperatures lead to different morphologies of the resulting carbon nanostructures. On the control sample and the sample subjected to heating to 100 °C, only nanofibers are formed, preheating to 150 °C leads to the formation of a porous structure with nanosized pores under the nanofibers, and preheating to 200 °C leads to a significant decrease in the porosity and concentration of nanofibers.